Case of a chronic ectopic pregnancy misdiagnosed as pelvic inflammatory disease - Sekar, Hashviniya (BMJ Case Rep, 2021)
The definition of a chronic ectopic pregnancy (CEP) is poorly defined in the literature and making a timely diagnosis can be incredibly challenging. This is primarily due to its broad range of clinical presentations and conflicting biochemical and sonographic results. Often, CEPs are mistaken for ovarian malignancies, pelvic inflammatory disease (PID), uterine fibroids or endometriosis, therefore, leading to a delayed diagnosis. We present a case report of a woman who was initially misdiagnosed with PID and then later preoperatively diagnosed with a CEP. This case particularly highlights the diagnostic dilemma posed by CEPs and raises awareness of the key clinical symptoms, biochemical and sonographic investigations which in combination can contribute towards making a timely preoperative diagnosis.